Plume-induced emissions of deep methane linked to the end-Guadalupian mass extinction - Sheng-Ao Liu; Zhili Xiong; Tianhao Wu; Mingyu Zhao (Nature Communications)
Abstract Methane (CH4) is a potent greenhouse gas, and massive CH4 emissions have the capacity to cause rapid and catastrophic climate effects. Here we report findings of large amounts of CH4 occurring as an important vapor phase in melt inclusions trapped by magmas in the plume-related Permian Emeishan large igneous province (LIP). Lines of evidence indicate that the CH4 is dominantly abiogenic and primarily had a mantle origin. Undegassed magmas are estimated to contain ~ 0.03% (by weight) CH4, which coincides with the relatively low oxygen fugacities of primary Emeishan LIP magmas. Our findings demonstrate that abiogenic CH4 can be generated in the mantle sources of a plume-related LIP, and that such CH4 could be brought into the surface by LIP magmatism and lead to strong warming. Quantitative models suggest that release of magmatic CH4 in the Emeishan LIP (7.4 × 103 Gt) had a significant contribution to the end-Guadalupian mass extinction.